2014
DOI: 10.1080/10538712.2014.896842
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Suicidal Ideations in Sexually Abused Female Adolescents: A 12-Month Prospective Study

Abstract: This study investigates the contribution of posttraumatic stress symptoms to the prediction of suicidality among female adolescent survivors of sexual abuse. A one-year prospective study of 52 female survivors aged 12 to 18 years was conducted. A negative binomial regression analysis revealed that depressive symptoms as well as posttraumatic stress symptoms associated with the sexual trauma were significant predictors of suicidal ideations a year later. Posttraumatic stress symptoms remained a significant pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 24 publications
0
14
0
1
Order By: Relevance
“…In this study, PTSD did not predict suicidal ideation when self-blame, shame, and depressive symptoms were included into the model. Self-blame and shame seem to be better predictors of suicidal ideation than PTSD in our sample, but note that Brabant et al (2014) used a 19-item measure of suicidal ideation and relied on a one year longitudinal design. A comprehensive measure and a longitudinal design may be necessary to assess the impact of PTSD on suicidal ideation.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…In this study, PTSD did not predict suicidal ideation when self-blame, shame, and depressive symptoms were included into the model. Self-blame and shame seem to be better predictors of suicidal ideation than PTSD in our sample, but note that Brabant et al (2014) used a 19-item measure of suicidal ideation and relied on a one year longitudinal design. A comprehensive measure and a longitudinal design may be necessary to assess the impact of PTSD on suicidal ideation.…”
Section: Discussionmentioning
confidence: 76%
“…Recently, Brabant, Hébert and Chagnon (2014) found that PTSD predicted suicidal ideation among sexually abused adolescent girls, even after controlling for depressive symptoms. In this study, PTSD did not predict suicidal ideation when self-blame, shame, and depressive symptoms were included into the model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these factors have not always yielded unequivocal results in predicting outcomes in sexually abused or assaulted youth (Brabant et al 2014). In addition, CSA severity is not amenable to change in treatment.…”
Section: Introductionmentioning
confidence: 99%
“…2 Rannsóknir hafa sýnt að kynferðislegt ofbeldi hefur ýmiskonar sálraen áhrif og eykur sjálfsvígshugsanir meðal unglinga, jafnvel óháð því hvort þau sýna jafnframt einkenni þunglyndis. 13,14 Einnig eru tengsl við vímuefnanotkun 15 og ýmiskonar geðraskanir 16,17 eins og þunglyndi, 18,19 kvíða 19 og áfallastreituröskun 20,21 vel þekkt. Rannsóknir á íslenskum unglingum hafa sýnt tengsl kynferðisof-beldis við baeði reiði og depurð.…”
Section: áGripunclassified